Kinetic modeling of transesterification of refined palm oil to produce biodiesel using Strontium Oxide(SrO)as a heterogeneous catalyst - Muhammad Fais, Haron (2013)
Biodiesel is an alternative source of energy to replace the fuel.Basically,biodiesel are vegetable oils and animal fats which undergoes a process to produce glycerol and fatty acid alkyl esters.In this study the transesterification process was performed using Strontium Oxide(SrO)as heterogeneous catalyst.The objective is to study the kinetic modeling of the transesterification of refined palm oil to produce biodiesel using SrO as a heterogeneous catalyst.The result show that the effect of catalyst concentration for 3.0 wt% of SrO concentration produced the highest concentration of methyl ester,0.78 mol/L while the effect of temperature,the temperature of 60⁰C obtained the highest concentration of methyl ester,0.84 mol/L at the end of the experiment.The function of ‘fminsearch’ was able to minimize the SSE of the data.The experimental data fit the ER model with the smallest value of SSE which 0.857 for effect of the catalyst concentration and 4.471 for effect of temperature. Therefore,the result supports that ER kinetics to be considered as the most appropriate model to use.